If [tex](a_n) \rightarrow 0[/tex] and [tex]\left|b_n - b\right| \leq a_n[/tex], then [tex](b_n) \rightarrow b[/tex].(adsbygoogle = window.adsbygoogle || []).push({});

I'm a little bit stuck on proving this! Part (iii) of the Order Limit Theorem states:

Assume:[tex]lim a_n = a[/tex] and [tex]lim b_n = b[/tex]

If there exists [tex]c \in[/tex]Rfor which [tex]c \leq b_n[/tex] for all [tex]n \in[/tex]N, then [tex]c \leq b[/tex]. Similarly if [tex]a_n \leq c[/tex] for all [tex]n \in[/tex]N, then [tex]a \leq c[/tex].

I can then take this to a point where [tex]b_n = b[/tex], but somehow that doesn't seem right because [tex]\left|b_n - b\right|<\epsilon[/tex], where [tex]\epsilon > 0[/tex]. Where am I going wrong here!

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Proving a limit and the Order Limit Theorem

**Physics Forums | Science Articles, Homework Help, Discussion**